2012
DOI: 10.1073/pnas.1106799109
|View full text |Cite
|
Sign up to set email alerts
|

Src tyrosine kinase phosphorylation of nuclear receptor HNF4α correlates with isoform-specific loss of HNF4α in human colon cancer

Abstract: Src tyrosine kinase has long been implicated in colon cancer but much remains to be learned about its substrates. The nuclear receptor hepatocyte nuclear factor 4α (HNF4α) has just recently been implicated in colon cancer but its role is poorly defined. Here we show that c-Src phosphorylates human HNF4α on three tyrosines in an interdependent and isoform-specific fashion. The initial phosphorylation site is a Tyr residue (Y14) present in the N-terminal A/B domain of P1-but not P2-driven HNF4α. Phospho-Y14 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(119 citation statements)
references
References 31 publications
5
109
1
2
Order By: Relevance
“…A small portion of the cross-talk PTMs were located far from each other; for instance, the phosphorylation on Y14 of HNF4␣ was distant from its cross-talk partners (i.e. phosphorylations on Y286 and Y288) (47). However, 130 of 193 (67.4%) PTM cross-talks in our data were located within 20 amino acids.…”
Section: Discussionmentioning
confidence: 47%
“…A small portion of the cross-talk PTMs were located far from each other; for instance, the phosphorylation on Y14 of HNF4␣ was distant from its cross-talk partners (i.e. phosphorylations on Y286 and Y288) (47). However, 130 of 193 (67.4%) PTM cross-talks in our data were located within 20 amino acids.…”
Section: Discussionmentioning
confidence: 47%
“…Immunohistochemical staining for HNF4␣ in liver, colon, and stomach cancers showed that there is a dysregulation of the HNF4␣ isoforms, with P2-HNF4␣ typically being expressed at higher levels than P1-HNF4␣ (18,34,35). Additionally, in a large cohort of 450 human colon cancer samples, we found a loss of nuclear P1-HNF4␣, which we attributed to Src tyrosine kinase preferentially phosphorylating P1-but not P2-driven HNF4␣ (17). The Cancer Genome Atlas (TCGA) recently identified the region encompassing HNF4A (20q13.12) as being one of several amplified loci in over 255 human colon cancers (36) and found an overexpression of the HNF4␣ protein in a subset of those samples (37).…”
mentioning
confidence: 85%
“…Mutations in the HNF4A gene or HNF4␣ binding sites have been linked to various human diseases, including an inherited form of type 2 diabetes (maturity-onset diabetes of the young 1 [MODY1]) and hemophilia (6,16). Recently, HNF4␣ was shown to be involved in colon cancer, but its precise role remains elusive (11,12,17,18).…”
mentioning
confidence: 99%
“…Due to historical reasons, research on the Src Family Kinase Src (SFKS) in carcinoma majorly focused on the fibroblasts of birds and mammals and human hematopoietic cells (Ma et al, 2012). Recently, many studies show that the abnormal overexpression of Src tyrosine kinase is associated with the occurrence of multiple epithelial-originated tumors, i.e., human colon carcinoma, breast carcinoma, and nonsmall cell lung carcinoma (Chellappa et al, 2012;Lv and Tian, 2012).…”
Section: Introductionmentioning
confidence: 99%